A numerical study of deep borehole heat exchangers in unconventional geothermal systems - Renaud, Théo (Cranfield University, 2018)
Poster presented at the Cranfield Doctoral Network Annual Event 2018.The geothermal energy sector is facing numerous challenges related to heat recovery efficiency and economic feasibility. Ongoing research on superheated/supercritical geothermal system, potentially representing a intensive amount of energy, is developed in Europe notably the Iceland Deep Drilling project (IDDP). The well IDDP-1, which reached a magma intrusion at a depth of 2100 m, raised new opportunities to untap the geothermal potential near shallow magmatic intrusions. Given their highly corrosive nature, geothermal fluids weaken the wellbore’s integrity during conventional geothermal production. Deep Borehole Heat Exchangers (DBHE) that do not require fluid exchange between the surface and the wells represent a strategic alternative to recovering heat from these unconventional geothermal resources, while minimising the risk of in-situ reservoir damage. The thermal influence and heat recovery associated with a hypothetical DBHE drilled into the IDDP geological settings were investigated via Computational Fluid Dynamics (CFD) techniques until 10 years of production, when the system reaches full equilibrium. Two wellbore designs were simulated, based on simplified geological properties from the IDDP-1 well description. The results show that, during the first year of production, the output temperature is function of the working fluid velocity before reaching pseudo-steady state behaviour. The cooling perturbation near the bottom hole is shown to grow radially from 10 to 40 m between 1 and 10 years of production, and the output thermal power calculated after 10 years reaches 1.2 MW for a single well.
Keywords: 'borehole heat exchange'; 'IDDP'; 'CFD'; 'CranfieldDN2018'